2012
DOI: 10.1134/s1070328412020078
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature preparation of tungsten halide clusters: Crystal structure of the adduct W5Br12 · SbBr3

Abstract: Single crystals of a new compound W 5 Br 12 ⋅ SbBr 3 (I) were isolated as a reaction product from the reduction of WBr 6 with elemental antimony at 250°C. The crystal structure was determined by single crystal X ray diffraction analysis. The structure contains square pyramidal tungsten clusters being linked into infi nite [(W 5 ) ] chains through shared W-Br a-a -W contacts of adjacent clusters. The structure of the adduct I can be viewed as an intercalation compound composed of double layers of cluster chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…The excitation spectrum recorded for this emission band (monitored at λ = 635 nm) reveals several bands with maxima at λ = 280 (4.43 eV), 335 (3.70 eV), 435 (2.85 eV), and 490 nm (2.53 eV). These emission‐band profiles and the large Stokes shift of 1.27 eV of (TBA) 2 [W 6 I 8 (O 3 SC 7 H 7 ) 6 ] are similar to those reported for (TBA) 2 [W 6 I 8 (CF 3 COO) 6 ] and the corresponding Mo cluster compounds , …”
Section: Resultssupporting
confidence: 83%
“…The excitation spectrum recorded for this emission band (monitored at λ = 635 nm) reveals several bands with maxima at λ = 280 (4.43 eV), 335 (3.70 eV), 435 (2.85 eV), and 490 nm (2.53 eV). These emission‐band profiles and the large Stokes shift of 1.27 eV of (TBA) 2 [W 6 I 8 (O 3 SC 7 H 7 ) 6 ] are similar to those reported for (TBA) 2 [W 6 I 8 (CF 3 COO) 6 ] and the corresponding Mo cluster compounds , …”
Section: Resultssupporting
confidence: 83%
“…[13] Our previous studies on WBr 6 have shown that antimony is most efficient in the reduction of WBr 6 , yielding W 6 Br 12 already at 350°C. [24] A combination of the reduction of WBr 6 and the cluster salt formation was performed by reacting appropriate stoichiometric proportions of WBr 6 , CsBr, and antimony at 550°C according to Equation (1). Reactants were loaded and fused into a silica tube and treated in a temperature gradient, thereby allowing SbBr 3 to sublime into the colder section of the ampoule.…”
Section: Articlementioning
confidence: 99%
“…Messerle has shown that the WCl 4 structure consists of polymeric chains of edge sharing, distorted bioctahedra with alternating short (2.688 Å ) and long (3.787 Å ) distances between the tungsten centers [1]. More recent work has confirmed a similar structure for WBr 4 with alternating short (2.794 Å ) and long (4.044 Å ) W/W distances [8]. The black WBr 4 solid displayed slight solubility in dichloromethane and 1,2-dichloroethane.…”
Section: Compound Characterizationmentioning
confidence: 59%
“…Preparations of WBr 6 have been reported through direct treatment of W(CO) 6 with liquid bromine [6][7][8] or via solid-state halide exchange reactions using WCl 6 and BBr 3 [9,10]. Preparation of WBr 5 proceeds from direct oxidation of tungsten metal using Br 2 at high temperatures (*600°C or higher) with subsequent isolation of the WBr 5 through repeated sublimation steps from a mixture that also contains WBr 6 [8,[11][12][13]. A more recent report indicates that heating of this mixed product under vacuum can yield pure WBr 5 [14].…”
Section: Introductionmentioning
confidence: 99%